2014
DOI: 10.24126/jobrc.2014.8.4.389
|View full text |Cite
|
Sign up to set email alerts
|

The genetic effect of N-methyl-N-nitro-N-nitrosoguanidine on callus induced from mature embryos of beans Phaseolus vulgaris

Abstract: This research was conducted to study the effect of the chemical mutagen N-methyl-N-nitro-N-nitrosoguanidine (NTG)on the chromosomes of callus induced from mature bean embryos, Harvester cultivar. Seeds were treated with 0.2 or o.4 mM of the mutagen that mixed with different percentages of ethanol for 24 hrs. Calli were induced on MS medium in the presence of 0.5 mg/L of Benzyl adenine (BA), 1 mg/L Indole acetic acid (IAA) and 100 mg/L from each of Casein hydrolysate, Glycine, Asparagine, Tyrosine, and Myo-Inos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Therefore from this result it has been recommended to use the last treatment for callus induction. The results of the current study are in agreement with what was reported by other researchers that the cultivars have different callus induction response in the presence of different hormone combinations (El-Kaaby et al, 2012;Shlahi, 2003).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore from this result it has been recommended to use the last treatment for callus induction. The results of the current study are in agreement with what was reported by other researchers that the cultivars have different callus induction response in the presence of different hormone combinations (El-Kaaby et al, 2012;Shlahi, 2003).…”
Section: Resultssupporting
confidence: 94%
“…Moreover tissue culture provides uniform environment for the selection under any stress. Combination of chemical mutation and in vitro selection has been used successfully by many researchers to select plants with desirable characteristics (Al-Hattab et al, 2002;Aslid et al, 2006;Shlahy and Al-Hattab, 2009a;Shlahy and Al-Hattab, 2009b). Therefore the current experiment was conducted to select tomato plants with good salt tolerance ability using in vitro chemical mutation and selection method.…”
Section: Introductionmentioning
confidence: 99%